Analysis of Information Literacy Skills in Student Essay Writing Using Mind Mapping - Frilia Shantika Regina; Vismaia S Damaianti; Yeti Mulyati; Andoyo Sastromiharjo (Studies in Learning and Teaching, 2024)
Information literacy is an ability that accommodates 21st-century skills. The aim of this research is to determine students' literacy skills in essays prepared with the help of mind mapping. This type of research is descriptive quantitative with the population namely students for the 2020/2021 academic year who have contracted the Criticism and Essay courses. This research analyzes student essays with assessment indicators containing aspects of information literacy based on the Association of College and Research Libraries (ACRL) with adjustments. The results showed that 41.17% were not yet competent, 47.05% were quite competent, and 11.78% were competent. Based on the research results, show that students' literacy skills expressed in essay form are still low. This was concluded because students were less proficient in developing a thesis, unable to modify information in their own words, and did not have written sources to support the statement. Apart from that, abilities at the phonological, morphological, and syntactic levels still need strengthening. Mind maps in essay writing can be combined with learning media to improve information literacy skills that can be described in essays.